Synthesis and characterization Of Ti based metal ceramic Matrix composites for Bioimplant - saxena, Vipul (IIT(BHU) Varanasi, 2022)
Abstract is available in the content
Keywords: Matrix composites; Ti based metal; Synthesis and characterization